Delinquent networks : youth co-offending in Stockholm - Sarnecki, Jerzy, 1947- (Cambridge studies in criminology (Cambridge University Press), 2001)
This book presents a study of co-offending relations among youths under 21 suspected of criminal offences in Stockholm during 1991-1995. Jerzy Sarnecki employs the method of network analysis of crime.